If Not For This - Fromm, Pete, 1958- (Book collections on Project MUSE., 2014)
After meeting at a boatman's bash on the Snake River, river runners Maddy and Dalt embark on a lifelong love affair. They marry on the banks of the Buffalo Fork, sure they'll live there the rest of their days. Forced by the economics of tourism to leave Wyoming, they start a new adventure, opening their own river business in Ashland, Oregon: Halfmoon Whitewater. They prosper there, leading rafting trips and guiding fishermen into the wilds of Mongolia and Russia. But when Maddy, laid low by dizzy spells, with a mono that isn't quite mono, both discovers she is pregnant and is diagnosed with multiple sclerosis, they realize their adventure is just beginning.